THE INFLUENCE OF SOLVENCY ON COMPANY STOCK RETURNS WITH LIQUIDITY AS A MODERATING VARIABLE - Rieneke Ryke Kalalo; Fitri Novilia; Andi Pangeran; Mustafa Mustafa; Gusnafitri Gusnafitri (ITB AAS Indonesia Surakarta, 2024)
Abstract The existence of investors is the most important thing for a company to continue to grow and develop. Investors will be more diligent in investing on a large scale if the results obtained or the reciprocity/share returns are also smooth. This research is a quantitative research with an exploratory approach. The data used in this research is secondary data obtained from the financial reports of RNI subsidiaries spread throughout Indonesia. The data obtained was analyzed with smart PLS 4.0. The research results show that first, the Solvency variable has a positive relationship and a significant influence on the Company Stock Return variable because the T-Table value is below the significance level of 0.05, namely 0.011. This means that the more debt a company has, the more investors will think the company has a big vision for growth. Second, Liquidity variables can moderate the Company Stock Return variable because the t-table value is positive and is below 0.05, namely 0.004. Even more significant than direct testing is 0.011. This means that even though investors believe in companies that can utilize debt to grow bigger, investors will believe again if this utilization is accompanied by smooth liabilities and total assets that continue to grow. Keywords : Solvency, Company Stock Return, Liquidity